Lipidomic markers of obesity and their dynamics after bariatric surgery - T. V. Saprina; A. S. Bashirova; V. V. Ivanov; S. I. Pekov; I. A. Popov; S. R. Bashirov; E. A. Vasilyeva; O. A. Pavlenko; D. V. Krinitskii; M. Chen (Бюллетень сибирской медицины)
Obesity is considered as a chronic progressive disease, heterogeneous in its etiology and clinical manifestations, and characterized by excess in body fat mass and its deposition in the body. The term “morbid obesity” refers to excessive deposition of adipose tissue with a body mass index (BMI) ≥40 kg / m2 or with a BMI ≥ 35 kg / m2 in the presence of serious complications associated with obesity. Along with obesity, the frequency of type 2 diabetes mellitus and cardiovascular diseases closely associated with it has increased. It results from the progression of metabolic disorders, including insulin resistance, which is inextricably linked with the accumulation of visceral fat and plays a key role in the pathogenesis of obesity-related diseases.The study of lipidomic signatures in obesity and associated conditions is a promising branch of fundamental medicine, which makes it possible to significantly and at a new conceptual level stratify a cohort of obese patients into various phenotypes, including a metabolically healthy and metabolically unhealthy obesity phenotypes. Dynamic changes in the lipidome both in the context of diet, drug treatment, and after various bariatric surgeries are of great interest for developing personalized strategies for the treatment of this disease. Currently available studies and their results suggest that we are only at the very start of studying this promising biomedical field.